PRAGMATICS STUDY ON POLITENESS DYNAMICS THROUGHOUT ORGANIZATIONAL HIERARCHIES - Liya Umaroh (Journal of Innovation Research and Knowledge, 2026)
This study is focused on the dynamics of language politeness used in local fast-food Industry particularly on handling complaint by hierarchical structure. Adopting pragmatic framework and Leech's Principle of Politeness, Brown & Levinson's face theory. The data were collected from various levels of the organization, from the top managerial level to operational staff. The result shows an inverse correlation between power and the burden of politeness principle in handling complaint . Informants at the CEO level tend to use the bald on record strategy and violate politeness maxims for the sake of policy efficiency. Conversely, informants at the middle level (Manager) use politeness as an instrument of diplomacy, while front line staff (Cashier and Crew) demonstrate compliance with the highest maxims through mitigation and humility strategies to reduce conflict. These results prove that politeness in a professional context is a functional instrument determined by organizational roles and managerial responsibilities, not just personal ethics.